PROFESIONALISME GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN MATEMATIKA DI SEKOLAH - Titis Dyah Dewi Narendradhuhita; Annisa Wulandari, Ikmawati Ikmawati, Zainuddin Untu (CV. ADIBA ASIHA AMIRA, 2025)
Educator professionalism is a crucial factor in enhancing the quality of education, particularly in mathematics instruction within educational institutions. Teachers are considered professionals when they possess not only a strong conceptual grasp of the content but also demonstrate the ability to implement innovative teaching techniques, adapt their methods to suit student needs, and effectively utilize technology and educational resources. This research aims to examine the impact of teacher professionalism on the enhancement of mathematics instruction in schools. The approach employed in this research is a literature review. The findings of the research indicate that educators with a strong sense of professionalism can enhance the quality of mathematics instruction in schools by fostering an engaging learning atmosphere and boosting students' motivation and comprehension of mathematical principles. Therefore, improving teacher professionalism through continuous training and competency development is a strategic step in efforts to improve the quality of mathematics learning in schools